2005
DOI: 10.1086/502566
|View full text |Cite
|
Sign up to set email alerts
|

Surgical-Site Infections Following Cesarean Section in an Estonian University Hospital: Postdischarge Surveillance and analysis of Risk Factors

Abstract: OBJECTIVES:To evaluate a multi-method approach to postdischarge sur veillance of surgical-site infections (SSIs) and to identify infection rates and risk factors associated with SSI following cesarean section.DESIGN: Cross-sectional sur vey. SETTING: Academic tertiar y-care obstetric and gynecology center with 54 beds.PATIENTS: All women who delivered by cesarean section in Tartu University Women's Clinic during 2002.METHODS: Infections were identified during hospital stay or by postdischarge sur vey using a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
3
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 23 publications
9
57
3
10
Order By: Relevance
“…8 Obstetric care services should be strengthened in rural areas. 59% of the patients were nulliparous which is similar to that of study in Mitt et al 9 Tran et al reported that the risk factor of surgical site infection was shown to be reduced by 39% and 60% when women had one or more children respectively. 10 Majority of the cases were unbooked which correlates with Amenu D et al study.…”
Section: Discussionsupporting
confidence: 83%
“…8 Obstetric care services should be strengthened in rural areas. 59% of the patients were nulliparous which is similar to that of study in Mitt et al 9 Tran et al reported that the risk factor of surgical site infection was shown to be reduced by 39% and 60% when women had one or more children respectively. 10 Majority of the cases were unbooked which correlates with Amenu D et al study.…”
Section: Discussionsupporting
confidence: 83%
“…Sustaining and developing local microbiology capacities are significant priorities in order to document the emergence of antimicrobial resistance. An achievement of this surveillance was to show the national and international community that a small- Our surveillance also underlines that an effective post-discharge surveillance is essential for ensuring accurate estimates of post-caesarean SSSI rate [26,27] and is feasible in limited-resource settings. Had we not implemented particular procedures after discharge to assess the wound healing process of patients (telephone call, follow-up visits), half of the cases would have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…1 The rates of SSI after cesarean section reported in the literature range from 3% to 15%, depending on the surveillance methods used to identify infections, the patient population, and the use of antibiotic prophylaxis. [2][3][4][5][6][7][8][9][10][11] The pooled mean rate of SSI after cesarean section for US hospitals participating in the Centers for Disease Control and Prevention's National Nosocomial Infections Surveillance System is 3.15%. 12 Expanding our knowledge of the risk factors associated with SSI is essential to developing targeted prevention strategies to reduce the risk of SSI.…”
Section: Infect Control Hosp Epidemiol 2008; 29:477-484mentioning
confidence: 99%